Custo de produção e lucratividade do cogumelo Agaricus Blazei nos padrões da agricultura sustentável: estudo de caso - Lima, Fernanda Silva (2017)
The objective of this study was to evaluate the costs of production and profitability of the sun mushroom (Agaricus blazei) in the patterns of sustainable agriculture. The analysis of production costs is extremely relevant for the analysis of the efficiency of the production of a given crop. To do so, the data were collected for the production of the year 2016. These data filled tables for calculations of total costs, total revenue and indicators of economic profitability. The A. blazei production system shows great economic viability according to the methods utilizes, since the liquid revenue is significantly positive, as the profitability index was 87,54%, with an operational profit of R$ 637.779,87/year. The variables that affected the profitability index were, in order of importance: sale price of the mushroom and productivity.